Analysis of the Effect of Economic Growth, Average Years of Schooling, and Regional Minimum Wage on the Open Unemployment Rate in Tuban Regency - Sinta Ayu Vironika; Marseto Marseto (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of economic growth, average years of schooling, and regional minimum wages on the open unemployment rate in Tuban Regency during 2004–2024. The study employs a quantitative approach using multiple linear regression analysis. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) of Tuban Regency and East Java Province. The dependent variable in this study is the open unemployment rate, while the independent variables consist of economic growth, average years of schooling, and regional minimum wages. The results show that economic growth has a negative effect on the open unemployment rate, indicating that higher economic growth can increase labor absorption. Average years of schooling also affect the open unemployment rate because higher educational attainment improves the quality of human resources and employment opportunities for the community. Meanwhile, regional minimum wages influence the open unemployment rate since wage increases may affect companies’ decisions in hiring labor. Simultaneously, all independent variables have a significant effect on the open unemployment rate in Tuban Regency.